Pemanfaatan Teknologi Informasi, Kualitas SDM, dan Sistem Pengendalian Intern Terhadap Kualitas Laporan Keuangan Studi pada OPD Provinsi Gorontalo - Mardiah Sikumbang; Lukman Pakaya; Harun Blongkod (Program Studi S1 Akuntansi Jurusan Akuntansi, Fakultas Ekonomi Universitas Negeri Gorontalo, 2020)
This research aimed to know the influence of the utilization of information technology, the quality of human resource, and the system of internal control towards the quality of financial statement at OPO of Gorontalo Province partially and simultaneously. This was quantitative research by using primary data obtained from the distribution of the questionnaire to the Regional Device Organization (ROO) personnel Gorontalo province. The data analysis technique used multiple regression analysis.This research finding revealed that the utilization of Information technology, the quality of human resource, and the system of internal control was simultaneously and significantly influenced the variable of quality of financial statement in ROO of Gorontalo Province with the determinant value as 64,40%. While the remaining was 35,600/0 could be described by other unlnvestigated variables such as the work commitment of the personnel. organization justice, education and training of the personnel, as well as the follow up of internal audit. While it was partially only the quality of human resource and the system of Internal control simultaneously and significantly influenced the variable of the quality of financial statemeot In the Regional Device Organization (ROO) of Gorontalo province.